Pengembangan Teknologi Wet Scrubber Untuk Meningkatkan Kualitas Lingkungan Pada Agroindustri - Hita, Muhammad Arga; Choiron, Miftahul; Firstandika, Leader (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Indonesia’s agroindustrial sector has experienced rapid growth in response to increasing demand for processed agricultural products; however, this development has also introduced environmental challenges in the form of air pollution from biomass combustion, such as sugarcane bagasse, tree branches, and organic waste. These combustion processes generate hazardous pollutants, including HCHO, TVOC, PM2.5, PM10, CO, and CO₂. This study aimed to develop and evaluate a wet scrubber system to reduce these emissions using three treatment methods: a water sprayer, a water trap, and a combination of both. Experiments were conducted using a mixture of sugarcane bagasse and organic waste with a combustion duration of 10 minutes and three replications for each treatment. Measured parameters included HCHO, TVOC, PM2.5, PM10, CO, CO₂, as well as water quality indicators (pH and TDS). Data were analyzed using ANOVA followed by Tukey’s HSD test. The results demonstrated significant reductions in HCHO (98.02%), TVOC (96.70%), CO (98.52%), and CO₂ (87.77%), with the combined method showing the best overall performance, although the effectiveness in reducing PM2.5 and PM10 remained limited. Overall, wet scrubber technology offers a practical and environmentally friendly solution for emission control in agroindustrial activities and supports the implementation of sustainable industrial practices.